Long-term shift towards shady and nutrient-rich habitats in Central European temperate forests - Vild, Ondřej; Chudomelová, Markéta; Macek, Martin; Kopecký, Martin; Prach, Jindřich; Petřík, Petr; Halas, Petr; Juříček, Michal; Smyčková, Marie; Šebesta, Jan; Vojík, Martin; Hédl, Radim (Wiley-Blackwell, 2024)
Biodiversity world-wide has been under increasing anthropogenic pressure in the past century. The long-term response of biotic communities has been tackled primarily by focusing on species richness, community composition and functionality. Equally important are shifts between entire communities and habitat types, which remain an unexplored level of biodiversity change. We have resurveyed > 2000 vegetation plots in temperate forests in central Europe to capture changes over an average of five decades. The plots were assigned to eight broad forest habitat types using an algorithmic classification system. We analysed transitions between the habitat types and interpreted the trend in terms of changes in environmental conditions. We identified a directional shift along the combined gradients of canopy openness and soil nutrients. Nutrient-poor open-canopy forest habitats have declined strongly in favour of fertile closed-canopy habitats. However, the shift was not uniform across the whole gradients. We conclude that the shifts in habitat types represent a century-long successional trend with significant consequences for forest biodiversity. Open forest habitats should be urgently targeted for plant diversity restoration through the implementation of active management. The approach presented here can be applied to other habitat types and at different spatio-temporal scales.
Keywords: biodiversity; forest succession; forest understory; global change; long-termchange; plant community; vegetation resurvey